MERANCANG MODEL SIMULASI SISTEM PENDUKUNG KEPUTUSAN SELEKSI PEMILIHAN CALON PEJABAT STRUKTURAL DI LINGKUNGAN UNIVERSITAS MENGGUNAKAN METODE AHP (ANALYTICAL HIERARCHY PROCESS) - Muliadi, Sari (JURNAL AKADEMIKA, 2016)
Decision Support Systemis adata processing systemto be used asinformation tosupport decision-makingofthissemi-structured, and unstructuredcurrentlyAnalitycalmethodHierarchy Process(AHP) is oneway ofdecision supportmethods. Many examplesof casesthat can beused indecision supportsystems, such as theselection ofelectionofficialsat the Universityof structuralwho had beenexecutedby a teamBaperjakat(Advisory Board Positionandrank), because ofsome ofthe criteriaandsub-criteria can be assessedas; CriteriaAspects ofPsychology(sectionvaluesââpsychology), workexperience criteria, criteriavaluesââof leadershiptraining, job performancecriteria, presentationsand interviewskriterifieldof structural position. The end result ofthisisa decision supportseistemposisdeterminestructural positionwithin theuniversitybased onthe criteriabeing assessed.